2020
DOI: 10.25174/2582-2675/2020/96419
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and its association with grain yield in wheat (Triticum aestivum L) under drought stress

Abstract: This study was designed to identify the drought tolerant and susceptible genotypes among 160 wheat genotypes. Analysis of variance under drought condition showed mean square due to genotypes had highly significant differences for all the quantitative traits in both years and pooled data, except flag leaf width, flag leaf area those were significant only and under control condition. Mean square due to genotypes had highly significant differences for all the traits in both the years and pooled data, except plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Verma et al (2019) observed comparable output with the number of ears per plant and biological yield per plant. Kumar et al (2020) found a positive relationship between the number of tillers per plant, spike length, test weight and the number of grains per spike and grain yield per plant.…”
Section: Resultsmentioning
confidence: 86%
“…Verma et al (2019) observed comparable output with the number of ears per plant and biological yield per plant. Kumar et al (2020) found a positive relationship between the number of tillers per plant, spike length, test weight and the number of grains per spike and grain yield per plant.…”
Section: Resultsmentioning
confidence: 86%
“…Drought stress can be simply defined as a scarcity of water which leads to dramatic changes in morphological, biochemical, physiological, and molecular features of the plants (Sallam et al, 2019;Kumar et al, 2020). All of these changes significantly hamper plant growth and crop production.…”
Section: Abiotic Stresses and Its Significancementioning
confidence: 99%
“…Conventional rice cultivation through flooding is also a major contributor to methane emission from the anaerobic decomposition of soil organic matter (SOM) (Liu & Wu, 2004). Additionally, weed flora in the rice-wheat rotation has changed dramatically with weeds of numerous species dominating the cropping system causing yield losses of 6-56% in rice and 20-40% in wheat (Kumar et al, 2008;Nawaz et al, 2019;Rabbani et al, 2011).…”
mentioning
confidence: 99%